Map of the islands of Lefkas, Cephalonia, Zante and the adjacent coast. - Jacques-Nicolas Bellin (Wikimedia Commons)
Notice visuelle issue de Wikimedia Commons pour la demo du fonds documentaire.
Licence Creative Commons Attribution 4.0 via Wikimedia Commons
Keywords: carte; plan; geographie; territoire; Wikimedia Commons